ANALISIS PENGANGKATAN CAMAT DI KABUPATEN BARRU PERSPEKTIF SIYASAH SYAR’IYYAH - Akmal, M. Rijal B.; Jafar, Usman; Natsif, Fadli Andi (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2023)
Hierarchically, the sub-district head as a district apparatus has a coordinating function in administering government in the sub-district area under the auspices of the regent through the district/city regional secretary. This study aims to analyze the appointment of sub-district heads in Barru District from the Siyasah Syariyyah perspective. The type of research used is qualitative research (field research) by taking data sources from the process of observation, interviews, documentation and literature studies. The results of the study show that the implementation of the appointment of sub-district heads as regional autonomous positions in Barru Regency has followed the qualifications for the post of sub-district heads mandated in laws and regulations by fulfilling technical competence, which is measured by the level of quality of education, technical training, and technical work experience as well as managerial competence. measured by the level of leadership experience. The appointment of sub-district heads in siyasa fiqh studies is not outlined textually but is emphasized in general in selecting leaders with the prerequisites of shiddiq, amanah, fathanah and tabligh.